2003
DOI: 10.1002/ejoc.200390141
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a New Neuritogenic‐Active Ganglioside from the Sea Cucumber Stichopus japonicus

Abstract: A new ganglioside molecular species SJG-2 has been obtained from the n-hexane-soluble lipid fraction of the chloroform/methanol extract of the sea cucumber Stichopus japonicus. On the basis of chemical and spectroscopic evidence, the structure of SJG-2 has been determined, as NeuAcα2Ǟ4(NeuAcα2Ǟ3)Galβ1Ǟ8NeuAcα2Ǟ3GalNAcβ1Ǟ 3Galβ1Ǟ4Glcβ1Ǟ1Cer. The new ganglioside SJG-2, possessing a unique carbohydrate moiety, is the first ganglioside containing either a branched sugar chain moiety or an N-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11] In the study of the GSLs of the sea cucumber Holothuria pervicax, we reported the isolation and structure of ten glucocerebrosides revealing a very close resemblance in structure.9) However, all these compounds still exist as a mixture of regio-isomers for terminal methyl groups in the side chain of the long-chain base (LCB) moiety, namely a mixture of iso and ante-iso isomers as shown in Fig. 1.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] In the study of the GSLs of the sea cucumber Holothuria pervicax, we reported the isolation and structure of ten glucocerebrosides revealing a very close resemblance in structure.9) However, all these compounds still exist as a mixture of regio-isomers for terminal methyl groups in the side chain of the long-chain base (LCB) moiety, namely a mixture of iso and ante-iso isomers as shown in Fig. 1.…”
mentioning
confidence: 99%
“…After Biological Assay Neuritogenic activity of 1 in PC12 cells was observed according to the method previously reported. 16) …”
Section: Gc-ms Analysis Of Fam From 1 a Fam Mixture From 1 Was Subjecmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14] In the study of the GSLs of the sea cucumber Cucumaria echinata (gumi in Japanese), we reported the isolation and structure of glucocerebrosides 2,4) and monosialogangliosides.…”
mentioning
confidence: 99%